(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: The anabolic effect of physical exercise on osseous tissue is related to mechanical effort, leading to the osteogenic response by causing dynamic changes, which stimulate osteocytes through fluid shifts in their canalicular network. They produce signaling molecules that regulate bone formation and absorption by osteoblast and osteoclasts. Objective: To study the effect of 8-week exercise training programs on the histomorphometry of male rat femur bone including weight, length, thickness and the bone formation biomarker (osteocalcin). Methods: The study was done in the labs of College of Medicine, Al-Nahrain University, from September 2019 to February 2020. A thirty adult healthy male rat (albino rat), were selected and divided into three groups; the group (A) of rats with exercise training programs of treadmill running, for 8 weeks. The control group, (B) were kept under free movements without exercise. The group (C) was kept under restricted movements in small cages. Tail blood sample were obtained twice from all animals; at zero day and after 8 weeks, for measurement of osteocalcin. Then after 8 weeks all animals were sacrificed and dissected for extraction of femoral bone for measuring bone length, weight, thickness and bone ultrastructure under light microscope by staining with hematoxylin and eosin. Results: The osteocalcin, femoral bone weight, length, thickness, haversian thickness and lamellar thickness showed significant increase in value of group A in comparison to group B and group C which show a significant decrease in femoral bone thickness, haversian thickness, lamellar thickness, and osteocalcin level. Conclusion: Exercise training has an anabolic effect on bone, in contrast to restriction movement that cause catabolic effect on bone. Osteocalcin increases with exercise and could be used as a marker in monitoring the exercise program therapy. Keywords: Femoral bone weight, length, thickness, haversian thickness, lamellar thickness, osteocalcin Citation: Musleh AM, Hashim ZH, Jaafar HA. Effect of 8-week exercise program on bone biomarker osteocalcin and bone histomorphometry features in male rats. Iraqi JMS. 2020; 18(2): 145-154. doi: 10.22578/IJMS.18.2.9.